Oral Cancer at a Glance - Saberian, Elham; Jenča, Andrej; Petrášová, Adriána; Jenčová, Janka; Atazadegan Jahromi, Reza; Seiffadini, Rahman (Asian Pacific Journal of Cancer Biology, 2023)
background: This review aims to serve as a comprehensive resource for healthcare professionals, researchers, and students interested in oral cancer, providing them with up-to-date information and insights into the current state of knowledge and practice in the field. Oral cancer, also known as mouth cancer, is a type of cancer that affects the mouth, tongue, lips, or throat. It is a common form of cancer worldwide, and its incidence is increasing annually. Oral cancer can be life-threatening if not detected early and treated promptly. Methods: We searched the PubMed database, Web of Science (WOS), Google Scholar, Scopus, and selected studies by predefined eligibility criteria. This review aims to provide an overview of oral cancer, including its causes, risk factors, signs and symptoms, diagnosis, treatment options, and prevention strategies. Result: Oral cancer is a preventable disease, and ongoing research is providing valuable insights into its risk factors and development. With this increasing knowledge, healthcare professionals have the opportunity to improve clinical outcomes by developing better early detection and treatment strategies. By staying up-to-date with the latest advancements in biomedical sciences and dentistry, they can make a significant impact on patient outcomes and save lives. Conclusion: summarizing the key points discussed in the review and highlighting the significance of continued research and awareness efforts to combat this complex and aggressive disease.